2018
DOI: 10.1089/hum.2017.238
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Virus Vector–Mediated Gene Therapy in China

Abstract: Due to the increased safety and efficiency of virus vectors, virus vector-mediated gene therapy is now widely used for various diseases, including monogenic diseases, complex disorders, and infectious diseases. Recent gene therapy trials have shown significant therapeutic benefits, and Chinese researchers have contributed significantly to this progress. This review highlights disease applications and strategies for virus vector-mediated gene therapy in preclinical studies and clinical trials in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Ad vectors have been studied extensively in tumor therapy trials 1 , 2 . In addition to the use of a conditionally-replicative Ad vector for head and neck cancer in China 3 , recent approval of an oncolytic herpesvirus-based treatment by the US Food and Drug Administration (FDA) raises optimism on the potential of viral vectors in cancer therapy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Ad vectors have been studied extensively in tumor therapy trials 1 , 2 . In addition to the use of a conditionally-replicative Ad vector for head and neck cancer in China 3 , recent approval of an oncolytic herpesvirus-based treatment by the US Food and Drug Administration (FDA) raises optimism on the potential of viral vectors in cancer therapy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the concept of gene therapy has been around for decades, clinical research only began in 1990 at the National Institutes of Health (Friedmann 1992), where a clinical study of a rare immunodeficiency disorder was conducted. Recently, gene therapy has begun to emerge as a medical research hotspot and clinical studies have been conducted for a wide range of diseases, including cancer (Culver and Blaese 1994), monogenic inherited disease (Tucci et al 2021), infectious disease (Peterson and Kiem 2018;Lin et al 2018), neurodegenerative disease (Sun and Roy 2021) and other diseases (Wolf, Mitalipov, and Mitalipov 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trial results 4,5 showed that rAd-p53 is effective against a variety of malignancies, including colon, glioma, lung, ovarian, and head and neck tumors. [6][7][8] We published an article on the clinical treatment of rAd-p53, 9 evaluated the efficacy of rAd-p53 (Gendicine Ò ) followed by chemotherapy in the treatment of uterine sarcoma.…”
Section: Introductionmentioning
confidence: 99%